Effect of intra row spacings on estimates of phenotypic and genotypic correlation coefficients in cotton (Gossypium arboreum) - AHUJA, S L; MONGA, D; MEENA, R A; KUMAR, RISHI; SAXENA, NEHA (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted on six Gossypium arboreum genotypes for two successive cropping seasons from 2011-2012 to 2012-2013 at Central Institute for Cotton Research, Regional Station, Sirsa, Haryana, India. The objective of the study was to evaluate the response and effect on estimates of phenotypic and genotypic correlation coefficients in G. arboreum cotton to variable intra row spacings of 67.5×10 cm, 67.5×20 cm and 67.5×30 cm having different plant densities. Correlations as well as direct effects of seed cotton yield with plant height were positive and high for averages of the two years in all the intra row spacings. In normal spacing of 67.5×30 cm significant and positive association of seed cotton yield were obtained for all the traits except boll weight. The results under three experiments of the spacing indicated that expression of association both at genotypic, phenotypic levels and direct effects were common for the traits plant height and boll weight in the three spacings. It is therefore concluded that while selecting for higher yields in any breeding programme irrespective of spacing emphasis should be placed on the higher plant height and higher bolls/plant. The values for direct effects in general were higher in normal spacing in comparison to other two closer spacings for all the traits, which let to conclude that in normal spacing improvement in yield in general can be made directly through improvement in the characters under this study.